The Effectiveness of Project-Based Learning Models On Students' Learning Outcomes in Fourth Grade: Animal Metamorphosis Modeling - Dewanti, Frisma Mufti Hafisyah; Nuswantoro, Agung Bangkit; Kurniati, Eva (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2024)
The aim of this study was to address the issue of low student learning outcomes in the Natural Sciences Subject, specifically in the "Animals Life Cycle" topic. The researchers sought to assess the effectiveness of the Project-based Learning (PjBL) model in improving learning outcomes. The study employed an experimental method with a "one-group pre-test-post-test design." Data was collected through tests, documentation, and observation. Tests were used to measure learning outcomes, observation was conducted to assess the implementation of the PjBL model, and documentation was employed to record students' progress. The study population consisted of fourth-grade students in one of the state elementary schools in Yogyakarta. The researchers used saturated sampling, meaning that all members of the population were included as samples. Data analysis involved the paired t-test and n-gain test. The findings revealed significant differences in student outcomes before and after the implementation of the treatment. The n-gain test demonstrated that the PjBL model effectively improved student learning outcomes.